1822. Clinical Outcomes Associated with Oral Beta-Lactam Therapy versus Oral Fluoroquinolones/TMP-SMX for Uncomplicated Gram-Negative Bacteremia. (15th December 2022) - Kaur, Satwinder S; Babic, Jessica T; Nguyen, Steven; Patel, Shivani
Abstract: Background: Agents commonly used as oral step-down therapy in Enterobacterales bacteremia include fluoroquinolones and TMP-SMX. The use of these oral agents have been associated with adverse events. Oral β-lactams are not recommended to treat Enterobacterales bacteremia because of concerns for sub-therapeutic serum concentrations. Given the limited data on clinical effectiveness of oral β-lactams and increased limitations with fluoroquinolones and TMP-SMX, oral β-lactams may be an alternative option. The purpose of this study is to evaluate the clinical effectiveness in patients transitioned to oral β-lactams versus fluoroquinolones or TMP-SMX for the step-down treatment of uncomplicated Enterobacterales bacteremia. Methods: A multi-center, retrospective, propensity-score matched, observational cohort study was conducted from July 1, 2017 to December 31, 2020, at 11 Memorial Hermann Health System hospitals among 690 patients with uncomplicated Enterobacterales bacteremia. Patients were included if they received > 1 day of intravenous antibiotic therapy followed by definitive oral step-down therapy with a β-lactam, fluoroquinolone, or TMP-SMX. The primary outcome was treatment failure within 30 days of starting oral antibiotics, defined as at least one of the following: recurrent bacteremia, transition to IV antibiotics, new-onset sepsis, 30-day readmission, or 30-day all-cause mortality. Results: After the patients were propensity score matched 1:1, a total of 199 patients with uncomplicated Enterobacterales bacteremia were included in each group. Treatment failure occurred in 8 patients (4%) who received β-lactams and 10 patients (5%) who received fluoroquinolones or TMP-SMX (OR, 0.79 [95% CI, 0.306-2.04] p -value 0.629). Median length of hospital stay was 5 days for both groups ( p -value 0.911), and median duration of oral antibiotics was 10 days in the fluoroquinolone or TMP-SMX group and 11 days in the β-lactam group ( p -value 0.377). Conclusion: Based on the results of this study, no significant difference in treatment failure was seen in patients who were transitioned to β-lactams versus fluoroquinolones or TMP-SMX as oral step-down therapy for uncomplicated Enterobacterales bacteremia. Oral β-lactams appear to be a safe and effective option. Disclosures: All Authors : No reported disclosures.